Salsola strobilifera (Chenopodiaceae), a new combination for a remarkable Australian taxon - Mosyakin, Sergei L. (Phytotaxa, 2019)
The new combination Salsola strobilifera is proposed for the morphologically remarkable Australian taxon originally described by Bentham as S. kali var. strobilifera (basionym). The latter name is lectotypified on a specimen from K (barcode K000899590) that was collected in New South Wales by Beckler during the Burke and Wills Victoria Exploring Expedition of 1860–1861, and was studied by Bentham for his Flora Australiensis. Earlier taxonomic treatments and other studies of “strobiliferous” native Australian plants (having short ovoid to almost globular strobile-like terminal inflorescences which are easily broken off at maturity) are briefly discussed and summarized. Judging from available morphological and partly molecular evidence, there are at least two “strobiliferous” morphotypes in Australia, one probably more closely related to S. australis sensu stricto and another more similar to S. sabrinae (= S. tragus subsp. grandiflora). It is concluded that Salsola sensu stricto is represented in Australia and adjacent islands by several (four or five, probably more) rather distinct native taxa that should be better recognized as separate species. On the basis of their morphological distinctiveness, these taxa are comparable to many other currently recognized Eurasian ones. The presence of Eurasian alien species also cannot be excluded. The need for a comprehensive study of Australian taxa of Salsola is emphasized.